REMEDIASI KESALAHAN SISWA MENYELESAIKAN SOAL SUHU DENGAN DIRECT INSTRUCTION BERBANTUAN VIDEO DI MTS ALMUHAJIRIN RASAU JAYA - Ade R. Ponda; Edy Tandililing; Hamdani Hamdani (Universitas Tanjungpura, 2018)
AbstractThis study aims to find a decrease in the number of mistakes of students of class VII Mts Almuhajirin Rasau Jaya in solving the temperature problem after remediated with video-assisted Direct Instruction model. Form of research in the form of pre-experimental design with One Group Pre-test-Post-test design. The sample consists of 15 students of class VII Mts Almuhajirin Rasau Jaya selected by intact group. Data collection tool in the form of essay tests consists of 5 Pre-test and 5 Post-test questions parallel problems. The validity score is 4 (= high) and the reliability of Pre-test is 0.699 (= high), and Post-test is 0.899 (= very high). Based on the data analysis for all types of errors there was a decrease of 58% with significance decrease based on the Chi Square test in the completion stage of writing the known χ2count (51,29)> χ2table (23,68); in the completion stage of writing the question asked χ2count (40,44)> χ2table (23,68); in the completion stage of writes the formula χ2count (57,27)> χ2table (23,68); and the completion stage of calculating χ2count (82,84)> χ2table (23,68); resulting in a decrease in the number of mistakes of students of class VII Mts Almuhajirin Rasau Jaya in solving the problem of temperature after remediated with video-assisted direct instruction model.Keywords: Remediation, Mistakes, Direct Instruction, Video, Temperature